The Effect of Organizational Competence and Commitment on Employee Performance on CV. Jati Visions Raya - Evalina; Herry Syafrial; Sandi Nasrudin Wibowo; Barra Purnama Pradja (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to determine the influence of organizational competence and commitment on employee performance on CV. Teak Visions Raya. The population of this study was CV employees. Teak Visions Raya. The technique used in determining the sample using random sampling samples, where the total population used as a sample was 73 respondents. The method in data collection uses multiple linear regression analysis. The results of this study show that there is a positive and significant influence between competence on employee performance with a calculated value of > ttabel 8.776 > 1.99394. There is a positive and significant influence between the organization's commitment to employee performance with a calculated value of > of 9.823 > 1.99394. And there is a positive and significant influence between organizational commitment and organizational commitment together on employee performance with a calculated value of > 67, 518 > 3, 13.